5-3(x-7)=2(2-x)8

Simple and best practice solution for 5-3(x-7)=2(2-x)8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3(x-7)=2(2-x)8 equation:


5-3(x-7)=2(2-x)8

We simplify the equation to the form, which is simple to understand
5-3(x-7)=2(2-x)8

Reorder the terms in parentheses
5+(-3x+21)=2*(2-x)*8

Remove unnecessary parentheses
+5-3x+21=+2+*(+2-x+)+*8

Reorder the terms in parentheses
5-3x+21=+(+4-2x)*8

Reorder the terms in parentheses
5-3x+21=+(+32-16x)

Remove unnecessary parentheses
+5-3x+21=+32-16x

We move all terms containing x to the left and all other terms to the right.
-3x+16x=+32-5-21

We simplify left and right side of the equation.
+13x=+6

We divide both sides of the equation by 13 to get x.
x=0.461538461538

See similar equations:

| 1/3x^2-1/6x+5/6 | | 2(3-4n)+2n=54 | | 3x+55=8 | | 3*-10-7*-10+35=15-2*-10 | | 4x^2-29x+37=-5x+10 | | x-1.8x=32 | | 2c-5= | | 4p+9+p-x+35x=-7 | | 9y^2-1= | | 33t-15= | | y/3.5+15=17 | | -18=18 | | (-n/7)=-50 | | -0.389y-0.974=6.789 | | (-n/9)=4 | | 6n=9-n | | 6r+5=8r+2-2r | | 6-7n=a | | 7y+9= | | 6r+5=8r+2+2r | | x^2-5x+7=3 | | 10a-2=20 | | 3x-17=180-122 | | 10+2=20 | | 2*5/-3-1=4+5*5/-3 | | -0.3d+(2.8)=-4 | | 4(7X+Y)=6 | | .59/.1= | | 8n+11=2y+29 | | .87/.3= | | 87-4x=14x+19 | | 12x-4(5y-2x)=0 |

Equations solver categories